2021
DOI: 10.3390/jcm10173832
|View full text |Cite
|
Sign up to set email alerts
|

Importance of In-Hospital Prospective Registry and Infectious Endocarditis Heart Team to Monitor and Improve Quality of Care in Patients with Infectious Endocarditis

Abstract: Aim: To investigate the value of prospective in-hospital registry data and the impact of an infectious endocarditis heart team approach (IEHT) on improvement in quality of care and monitor outcomes in hospitalized patients with IE. Methods: Between December 2014 and the end of 2019, 160 patients were hospitalized in one centre with the definite diagnosis of infectious endocarditis (IE) and entered in a prospective registry. From 2017, an IEHT was introduced. Propensity score matching was used to assess the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Each observed that MDT management was still associated with reduced mortality after adjusting for the calendar year. Two studies [ 22 , 32 ] also performed an analysis with propensity score matching between cohorts; both revealed a reduction in mortality with MDT management.…”
Section: Resultsmentioning
confidence: 99%
“…Each observed that MDT management was still associated with reduced mortality after adjusting for the calendar year. Two studies [ 22 , 32 ] also performed an analysis with propensity score matching between cohorts; both revealed a reduction in mortality with MDT management.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have analysed cohorts of patients treated in hospitals without heart surgery facilities, highlighting cohorts with a lower mortality rate than that which is usually published (19%). They also found that the creation of a multidisciplinary working group and the implementation of protocols reduces this figure even further (8-14%) [11,[25][26][27][28][29]. A more recent cohort suggests that patients treated in secondary centres may be older and have more comorbidities [30].…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, it is essential to implement agreed protocols adapted to the characteristics of each hospital and to draw up user-friendly guidelines, benefitting from the services of at least one clinical consultant specialising in infectious diseases in secondary hospitals. The active participation of the infectious disease consultant has been associated with better outcomes in patients with bacteraemia and endocarditis, specified in various guidelines as being an alternative-almost mandatory-in the diagnostic and therapeutic assessment and during the monitoring of these patients [11,[25][26][27][28][29]32]. Unsuitable antibiotic therapy is a particularly relevant factor, as it can be modified.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is based almost exclusively on imaging and primarily on echocardiography. Conversely, the endocarditis team approach has improved patient outcomes [ 69 , 70 ]. Notwithstanding, two recent European surveys showed that the presence of an endocarditis team is still not dominant and comprises a specialist in echocardiography only in 2/3 of the cases [ 22 , 71 ].…”
Section: Conclusive Remarksmentioning
confidence: 99%